Strategi Pemberdayaan Subak Abian Giri Amerta dalam Menunjang Agrowisata di Desa Kerta, Kecamatan Payangan, Kabupaten Gianyar - DWIGUNA, ANAK AGUNG GEDE ANGGA; DIARTA, I KETUT SURYA; SARJANA, I MADE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2024)
Empowerment Strategy of Subak Abian Giri Amerta in Supporting Agrotourism in Kerta Village, Payangan District, Gianyar Regency. Community empowerment is an effort to empower the community through the realization of their potential capabilities. But the problem is that there are interna l factors and external factors that have not been optimized, causing problems in all the resources and potential that have not been able to be utilized in this case to support agro-tourism.This research analyzes the internal factors and external factors that affect Subak Abian Giri Amerta in supporting Agro-tourism in Kerta Village, Payangan District, Gianyar Regency, and designs a strategy for empowering Subak in supporting agro- tourism.(IFAS, Internal Strategic Factor Analysis Summary), matrix of external strategic factors (EFAS, Ekternal Strategic Factor Analysis Summary, SWOT analysis matrix I-E analysis falls into cell II, where this strategyrequires Subak Abian Giri Amerta to develop its agricultural tourism attractions and agro-tourism facilities. The SWOT analysis resulted in four alternative strategies, namely: (a) SO strategy (expansion of the tourism market, working together to develop infrastructure), (b) ST strategy (increasing the productivity of agricultural products, developing subak facilities), (c) WO strategy (optimizing aspects of agro-tourism support, min improve human resources in agro-tourism services), and (d) WT strategy (strict rules to control land conversion, optimize supporting facilities and infrastructure to be able to compete).